Education research and the media : challenges and possibilities - Baroutsis, Aspa; Riddle, Stewart; Thomson, Pat (Routledge, 2019)
"Universities around the world now actively encourage academics to engage in public scholarship, publishing in traditional and new media - newspapers, television, radio, blogs and social media. Education, Research and the Media addresses this situation, using empirical and reflexive accounts, to interrogate and advance the ways in which this shift is usually discussed. Drawing on Australian and international scholars and contexts, this edited collection probes the effects of these engagements. Taken together, the book offers new conceptualisations of the junctures and disjunctures of local, national and transnational mediascapes in education research, working across both traditional media and social media platforms. The book takes as its starting point that traditional national media, while still significant, is now embedded in practices and discourses that transcend geographic and spatial boundaries. Global media logics challenge the profitability and operations of media corporations, as the production of news and information is paradoxically both democratised and fragmented. There is a limited body of research about how this mediatised landscape impacts on public scholarship. This is the first book in the field of education to systematically investigate this landscape, using empirical examples and analysis, as well as a range of theoretical and conceptual approaches"--